Determination of αS using OPAL hadronic event shapes at √s=91--209 GeV and resummed NNLO calculations - Abbiendi, Giovanni; Bock, Peter (The European physical journal. C, Particles and fields, 2011)
Hadronic event shape distributions from e+e− annihilation measured by the OPAL experiment at centre-of-mass energies between 91 GeV and 209 GeV are used to determine the strong coupling αS. The results are based on QCD predictions complete to the next-to-next-to-leading order (NNLO), and on NNLO calculations matched to the resummed next-to-leading-log-approximation terms (NNLO + NLLA). The combined NNLO result from all variables and centre-of-mass energies is while the combined NNLO + NLLA result is The completeness of the NNLO and NNLO + NLLA results with respect to missing higher order contributions, studied by varying the renormalization scale, is improved compared to previous results based on NLO or NLO + NLLA predictions only. The observed energy dependence of αS agrees with the QCD prediction of asymptotic freedom and excludes the absence of running.